Specific IgA antibodies in the diagnosis of acute brucellosis - Hanan El-Mohammady; Hind Ibrahim Shaheen; John David Klena; Isabelle Antoun Nakhla; Mattew A Weiner; Adam Wilson Armstrong (Journal of Infection in Developing Countries)
An Egyptian female with night sweats, headache, and back pain was diagnosed with acute brucellosis one week after returning from a North African country. Humoral immune responses to specific immunogenic proteins were investigated before and after treatment. ELISA was performed to detect levels of specific antibody (Ab) titers. Immunoblot analysis of Ab recognizing specific Brucella antigenic bands was also performed. IgA was detected on the day of disease onset. Specific agglutination titer was 1:160; it doubled three days later and treatment was implemented. Blood culture yielded Gram-negative coccobacilli after one month, confirmed as B. melitensis by AMOS-PCR. Immunoblotting revealed IgM Abs against two protein bands of 112 and 130-kDa observed only during the acute stage. On the other hand, the intensity of IgG Abs against 21 and 21.5-kDa protein bands positively correlated with the time of convalescence. Based on our observations we conclude that specific IgA levels may be used as an early diagnostic marker for Brucella and high molecular weight protein bands may be useful in the differentiation between acute and chronic brucellosis.